Lung function abnormalities in infants developing bronchopulmonary dysplasia. Issue 11 (10th September 2011) - May, Caroline; Kennedy, Caroline; Milner, Anthony D; Rafferty, Gerrard F; Peacock, Janet L; Greenough, Anne
Abstract : Objective: To determine if infants developing bronchopulmonary dysplasia (BPD), particularly mild BPD, initially had minimal lung function abnormalities, which then worsened throughout the neonatal period. Design: Prospective observational study. Setting: Tertiary neonatal intensive care unit. Patients: 74 infants with a median gestational age of 30 weeks (24–32) and birth weight of 1200 g (474–2000) were studied; 35 had no BPD, 12 developed mild BPD and 23 developed moderate/severe BPD. Interventions: BPD was diagnosed in infants who were oxygen dependent beyond 28 days after birth. Main Outcome Measures: Lung function was assessed by measurement of functional residual capacity (FRC) by helium gas dilution and compliance and resistance of the respiratory system. Measurements were attempted on days 3, 5, 7, 14, 21 and 28. Results: Infants developing BPD, particularly moderate/severe BPD, had lower mean FRC (p=0.009) and mean compliance (p=0.005) throughout the 28-day period than those who did not develop BPD. Lung function improved over the neonatal period in all three groups, but the rate of improvement in FRC (p=0.004) and compliance (p=0.002) results over the first 28 days varied by BPD status, being greatest in infants developing moderate/severe BPD (all p values <0.05). Conclusions: Overall, in infants who did and did not develop BPD, lung function improved throughout the neonatal period. Infants with more severe initial lung disease were more likely to develop moderate/severe BPD.